Overriding plate, mantle wedge, slab, and subslab contributions to seismic anisotropy beneath the northern Central Andean Plateau. (13th July 2016) - Long, Maureen D.; Biryol, C. Berk; Eakin, Caroline M.; Beck, Susan L.; Wagner, Lara S.; Zandt, George; Minaya, Estella; Tavera, Hernando
Abstract: The Central Andean Plateau, the second‐highest plateau on Earth, overlies the subduction of the Nazca Plate beneath the central portion of South America. The origin of the high topography remains poorly understood, and this puzzle is intimately tied to unanswered questions about processes in the upper mantle, including possible removal of the overriding plate lithosphere and interaction with the flow field that results from the driving forces associated with subduction. Observations of seismic anisotropy can provide important constraints on mantle flow geometry in subduction systems. The interpretation of seismic anisotropy measurements in subduction settings can be challenging, however, because different parts of the subduction system may contribute, including the overriding plate, the mantle wedge above the slab, the slab itself, and the deep upper mantle beneath the slab. Here we present measurements of shear wave splitting for core phases ( SKS, SKKS, PKS, and sSKS ), local S, and source‐side teleseismic S phases that sample the upper mantle beneath southern Peru and northern Bolivia, relying mostly on data from the CAUGHT experiment. We find evidence for seismic anisotropy within most portions of the subduction system, although the overriding plate itself likely makes only a small contribution to the observed delay times. Average fast orientations generally trend roughly trench‐parallel to trench‐oblique, contradicting predictions from the simplest two‐dimensional flow models and olivine fabric scenarios. Our measurements suggest complex, layered anisotropy beneath the northern portion of the Central Andean Plateau, with significant departures from a two‐dimensional mantle flow regime. Key Points: We measure shear wave splitting beneath southern Peru and northern Bolivia to constrain seismic anisotropy Evidence for contributions from the mantle wedge, subducting slab, and subslab mantle, with a weak contribution from the overriding plate Observations contradict predictions from simplest flow models and olivine fabric scenarios, suggesting complex mantle flow and deformation